Penguatan Kelembagaan Kampung Adat sebagai Kampung Tematik - Ratih Ratih; Kusdarini Kusdarini; Hendri Koeswara; Malse Yulivestra; Ilham Aldelano Azre (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Rimbo Tarok Traditional Village was designated as a Thematic Village of Padang City in 2021; however, until 2024, its development remains stagnant, and it has yet to gain wider recognition as a tourist destination and creative economy hub. The primary issue lies in the suboptimal management of the Tourism Awareness Group (Pokdarwis), stemming from a limited understanding of institutional functions and a lack of digital promotion strategies. This study aims to analyze the weaknesses of institutional management and formulate strengthening strategies based on collaboration and digital promotion. A qualitative case study approach was employed, involving interviews, observations, and documentation, with the head and members of Pokdarwis. The findings reveal that Pokdarwis lacks a structured management system, stakeholder coordination remains weak, and the use of social media is underutilized. Institutional strengthening programs through socialization, management training, and engagement with external partners proved to enhance members’ understanding of organizational roles and opened opportunities for cultural tourism promotion. In conclusion, strengthening institutional capacity and utilizing digital promotion are strategic steps to develop Rimbo Tarok Traditional Village into a competitive cultural tourism destination that contributes to improving the local community’s economy.